Oligopeptide self-assembly: mechanisms, stimuli-responsiveness, and biomedical applications - Ge, Lei (2024)
Oligopeptide self-assembly materials have emerged as a promising class of biomaterials with diverse applications in biomedicine. This review highlights the recent progress in comprehending the self-assembly mechanisms intrinsic to oligopeptides and their behavior in response to specific stimuli. By methodically structuring the amino acid sequence and managing external stimuli, such as pH levels, redox conditions, or enzymatic activity, we can exercise unprecedented control over the self-assembly process. This manipulation results in structures of extraordinary versatility, including micelles, nanofibers, and coacervate droplets, each possessing modifiable mechanical and chemical properties. Furthermore, these self-assembled constructs demonstrate immense potential within varied biomedical applications. The stimuli-sensitive nature of oligopeptide assembly materials facilitates the timely encapsulation and release of therapeutic cargos, consequently eliciting desired cellular responses. This approach paves the way for more precise tumor targeting, personalized medicinal treatments, and well-regulated drug dispensation. Their innate biocompatibility and proficiency in replicating the extracellular matrix render them ideally suited for applications such as tissue engineering, wound remediation, and regenerative medicine. In summary, oligopeptide self-assembling materials show tremendous potential as adaptable platforms for cutting-edge biomedical applications, thereby bridging the divide between fundamental research and practical clinical application.